The Impact of Artificial Intelligence on the Evolution of Ad vanced Cities: An Empowered Future - Florian Villegas, Renzo (2025)
This scientific study focuses on a literature review on the use of Artificial Intelligence (AI) and its impact on the different key sectors that make up a city. Highlighting the benefits of its implementation and the challenges faced by governments for its regulation and control. For this purpose, 9 scientific articles were selected that address the topics that will be discussed throughout this article: politics, transportation, citizen security, education, labor and health. The aim is to show the benefits of AI implementation in these sectors that will guide us towards a modern future where AI prevails as an irreplaceable tool.